2017
DOI: 10.1111/jmi.12545
|View full text |Cite
|
Sign up to set email alerts
|

Unifying miscellaneous performance criteria for a prototype supercapacitor via Co(OH)2 active material and current collector interactions

Abstract: The use of transition metal oxides and hydroxides in supercapacitors can yield high specific capacity electrodes. However, the effect of interaction between active material and current collector has remained unexplored. Here the behaviour of electrodeposited hexagonal cobalt hydroxide nanosheets on a variety of substrates was investigated, and the resulting valence bonding, morphological evolutions and phase transformations examined. It is shown that the electrochemical activity of the face centred cubic (FCC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…With the significant increase in the consumption of portable electronic devices, electric vehicles and mobile phones, supercapacitors (SCs) have recently drawn much attention due to their ultrahigh power density, long-span cycle life, lightweight and environment friendliness [1][2][3][4][5]. The currently available SCs, although able to possess versatile features, only have an energy density that is one to two orders of magnitude lower than that of a typical rechargeable ion battery [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…With the significant increase in the consumption of portable electronic devices, electric vehicles and mobile phones, supercapacitors (SCs) have recently drawn much attention due to their ultrahigh power density, long-span cycle life, lightweight and environment friendliness [1][2][3][4][5]. The currently available SCs, although able to possess versatile features, only have an energy density that is one to two orders of magnitude lower than that of a typical rechargeable ion battery [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the specific capacitance of Ni(OH) 2 @NPG/Ni foam electrode showed a rapid loss of about 31.2% of its initial value in the first 1,000 cycles and then remained relatively constant in the subsequent 4000 cycles, in comparison with a serious 64% capacitance loss of the Ni(OH) 2 @Ni foam electrode after 1,000 cycles under the same conditions. As reported in a previous study, the choice of substrate has a significant effect on the cyclic stability of the electrode material, and Ni foam substrate is regarded as an inferior substrate to exhibit a poor cyclic stability for the TMOH-based electrode material since the formation of nickel oxide on the Ni foam surface leads to increased resistance between the electrode material and the current collector [41]. With NPG decoration on Ni foam, the R s for Ni(OH) 2 @NPG/ SCIENCE CHINA Materials.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, the specific capacitance of the Ni(OH) 2 @NPG/Ni foam electrode remains 1,645 F g -1 at a scan rate of 50 mV s -1 . The current collector plays a very important role in the electrochemical performance of the electrode material [41][42][43]. Such ultrahigh specific capacitance and excellent rate capability of the Ni(OH) 2 @NPG/Ni foam electrode could be mainly attributed to the significantly enhanced charge transport benefiting from the seamlessly integrated binder-and additive-free electrode with 3D hierarchical micro/nanoporosity, which makes full use of the conformally wrapped Ni(OH) 2 nanoflakes on the high surface area NPG/Ni foam composite current collector.…”
Section: Resultsmentioning
confidence: 99%
“…Consider the semiconductor nature of Co 3 O 4 , the increase of thickness may induce decrease of rate capacity. So proper deposition time has been chosen [32] . Then, the Co 3 O 4 /CFP composite is obtained by calcining Co(OH) 2 /CFP through a high temperature treatment, and the CFP remains stable at this temperature (Fig.…”
Section: Resultsmentioning
confidence: 99%